A squalodontid whale from the early Miocene near Blanchetown, South Australia. Issue 1 (2nd January 2020) - Pledge, Neville S.
ABSTRACT: The discovery and collection of a fragmentary skeleton found in cliffs of the early Miocene Mannum Formation near Blanchetown, on the River Murray in South Australia, are recounted, and the specimen identified as that of a rare squalodontid whale, on the basis of a near-complete mandible retaining two dentate, triangular posterior teeth.